Vegetable revelations : inspiration for produce-forward cooking - Satterfield, Steven; Slonecker, Andrea (Harper Wave, an imprint of HarperCollinsPublishers, 2023)
"Discover new ways to serve a wide range of vegetables with this cookbook featuring over 150 recipes from Steven Satterfield, the James Beard Foundation Award-winning chef and author of Root to Leaf"--